Digital Tools for Heritage Protection and Conservation in Conflict-Prone Areas: A Glympse from Northeastern Africa and the Horn - Filosa, Domenico; Sernicola, Luisa; Manzo, Andrea (Archeologie tra Oriente e Occidente, 2025)
Northeastern Africa and the Horn are universally recognized as a melting pot of cultures and civilizations with a rich and diverse archaeological heritage paralleled by sumptuous packages of languages, traditions and systems of knowledge. Unfortunately, the area is also prone to recurrent political crises and social tensions that often escalate into long periods of armed conflicts. The impact on tangible heritage is always extremely severe. Sites, museums and cultural centres are intentionally or accidentally targeted by drone attacks, looted or severely damaged by lack of infrastructure and land maintenance. Objects are destroyed, dispersed or entered into the illegal trafficking circuit. Intangible heritage is also heavily compromised. The loss of lives and the migration of people contributes to the disappearance of systems of knowledge impossible to recover and pass on. In such areas, issues related to protection strategies for cultural heritage should become a crucial component in the agenda of archaeological research programs. Based on our experience in Egypt, Ethiopia and Sudan, this paper will discuss a set of digital tools useful to adopt when working in conflict areas. Special attention will be given to the role that virtual museums can play in such regions.